Early immune surveillance to predict cytomegalovirus outcomes after allogeneic hematopoietic stem cell transplantation - Xia, Jintao; Li, Xuejie; Gui, Genyong; Wu, Jian; Gong, Shengnan; Shang, Yuxin; Fan, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Background There is no method of predicting human cytomegalovirus (HCMV) outcomes in allogeneic hematopoietic stem cell transplant recipients clinically, leading in some cases to excessive or insufficient antiviral therapy. We evaluated the early immune response of recipients with disparate HCMV outcomes. Methods The HCMV outcomes of recipients were determined by long-term monitoring of HCMV DNA levels posttransplant. HCMV IgG and IgM concentrations at 1 week before and 1 week after transplantation, absolute lymphocyte counts, and HCMV-specific IFN-γ secreting cells at 1 month posttransplant were evaluated based on HCMV outcome. Results All recipients were negative for HCMV IgM. Significant differences between recipients with and without HCMV reactivation were observed in pre- and post-transplant HCMV IgG antibody levels, absolute lymphocyte counts, and HCMV-specific IFN-γ secreting cells (P < 0.05). HCMV IgG antibody levels significantly increased after transplantation in recipients with HCMV reactivation (P = 0.032), but not in those without reactivation. Multivariate analysis revealed that except for the absolute lymphocyte count these biomarkers were related to HCMV reactivation, independent of other clinical factors. In time-to-event analyses, lower levels of these biomarkers were associated with an increased 150-day cumulative incidence of HCMV reactivation (log-rank P < 0.05). In recipients with HCMV reactivation, the duration of HCMV DNAemia had negative correlation with HCMV-specific IFN-γ-secreting cells (P = 0.015, r = -0.372). The relationships between the peak HCMV DNA load and absolute lymphocyte count and HCMV-specific IFN-γ-secreting cells followed the same trends (P = 0.026, r = -0.181 and P = 0.010, r = -0.317). Conclusions HCMV IgG, absolute lymphocyte count, and HCMV-specific IFN-γ secreting cells represent the humoral and cellular immune response. Early monitoring of these immune markers could enable prediction of HCMV outcomes posttransplant and assessment of the severity of HCMV DNAemia.